Early detection for server availability in University Malaya data center / Mohd Azizi Osman - Osman, Mohd Azizi (2016)
Early detection for server availability in UM Data Center is developed specifically for the Data Center department in University of Malaya. This system is generally to facilitate the process of the administrators to manage servers and make it more efficient and effective. The current system has been used manually to monitor the servers and many changes need to fulfill current requirement. The objective of the system is to design the detection algorithm for server availability, to develop the detection algorithm for server availability and to test the detection algorithm form server availability. This scripts will monitor some of the servers performance and able to send notification to the administrators via email and SMS prior to the occurrence of errors in servers of the servers.